Enhancing Lovastatin Biosynthesis in Oyster Mushrooms (Pleurotus ostreatus) using Phytohormones - Mustafa, Fransisca Astrid; Kandar, Mamat; Aryantha, I Nyoman Pugeg (Makara Journal of Science, 2023)
The biosynthesis of lovastatin, the anti-cholesterol compound, in oyster mushrooms (Pleurotus ostreatus), has the potential to be enhanced by utilizing phytohormones, which activate the expression of certain genes. This research aimed to determine the best type and concentration of phytohormone among auxin, gibberellin, and cytokinin, as well as the best mycelial colonization percentage in F2 medium to realize the greatest increase in lovastatin biosynthesis in oyster mushrooms. Lovastatin was extracted from the fruiting bodies and mycelia and analyzed by spectrophotometry. The analysis of CYP450 linked to lovastatin biosynthesis was conducted by quantitative polymerase chain reaction (qPCR) using samples containing the highest concentration of lovastatin. The results showed that adding phytohormones increased the lovastatin concentration in the fruiting bodies and mycelia of P. ostreatus. The highest lovastatin content was observed in the 10 ppm gibberellin treatment by applying 75% mycelial colonization in the F2 medium. Furthermore, this gibberellin treatment also demonstrated increased expression of the CYP450 gene in the fruiting bodies and mycelia. In conclusion, phytohormone treatments with the right timing and appropriate concentration increased lovastatin biosynthesis in P. ostreatus as well as related gene expression.